1993
DOI: 10.1038/364725a0
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of dystrophin in transgenic mdx mice eliminates dystrophic symptoms without toxicity

Abstract: Duchenne and Becker muscular dystrophy (DMD and BMD) are X-linked recessive diseases caused by defective expression of dystrophin. The mdx mouse, an animal model for DMD, has a mutation that eliminates expression of the 427K muscle and brain isoforms of dystrophin. Although these animals do not display overt muscle weakness or impaired movement, the diaphragm muscle of the mdx mouse is severely affected and shows progressive myofibre degeneration and fibrosis which closely resembles the human disease. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
178
1
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(190 citation statements)
references
References 24 publications
10
178
1
1
Order By: Relevance
“…Administration of minigene resulted in a high proportion (up to 25%) of ssDPM; this is comparable to the transfection efficiency of the most successful experiments with dystrophin gene transfer into mdx mice. 4,5,16 Absence of any signs of degeneration proved the viability of all these transfected fibers. Higher efficiency of minigene transfection compared with full-length gene cDNA might be partly explained by almost twice the difference in their molecular weights (6.3 and 12 kb) and thus by the higher copy number of minigene cDNA in the same volume of microspheres.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Administration of minigene resulted in a high proportion (up to 25%) of ssDPM; this is comparable to the transfection efficiency of the most successful experiments with dystrophin gene transfer into mdx mice. 4,5,16 Absence of any signs of degeneration proved the viability of all these transfected fibers. Higher efficiency of minigene transfection compared with full-length gene cDNA might be partly explained by almost twice the difference in their molecular weights (6.3 and 12 kb) and thus by the higher copy number of minigene cDNA in the same volume of microspheres.…”
Section: Discussionmentioning
confidence: 92%
“…16 It is also postulated that phenotypic correction of DMD requires restoration of about 20% of normal dystrophin levels in affected dystrophic muscles. 15,17 This level of dystrophin gene expression in limb muscles has recently been achieved in mdx mice transduced with a new type of adenoviral vector 4 and this approach looks especially promising when supplemented with transient immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown schematically in Figure 3, pMA⌬ was constructed using left and right end genomic clones pG1HAX and pG11SAB, which had unique ApaLI sites engineered immediately flanking the end of the MAV-1 DNA sequences (GE Carney and KR Spindler, unpublished data). Our initial attempts using the pBSX-based plasmids 25 yielded some clones that were unstable and tended to lose MAV-1 DNA over time. Since large plasmid clones can be toxic to bacterial host cells at high copy numbers, 26 we chose to use plasmid pWSK29 26 as vector for our construction because it is derived from the low copy number pSC101 replicon (about five copies per cell).…”
Section: Construction Of Plasmids By Bacterial Homologous Recombinationmentioning
confidence: 99%
“…2 We and others have demonstrated that replacement of dystrophin in transgenic mdx mice restores normal expression of the dystrophinglycoprotein complex and prevents skeletal muscle pathology from developing. 3,4 Also, delivery of full-length and some truncated dystrophins to adult skeletal muscles using viral vectors has been shown to reverse partially the dystrophic pathology in mdx limb muscles. 2,[4][5][6] Successful gene and cell therapy for DMD will require sustained dystrophin expression in skeletal and cardiac muscles.…”
Section: Introductionmentioning
confidence: 99%